Answer:
12
Step-by-step explanation:
2 : 6 pencil : eraser
? : 36
36 divided 6 = 6
so to get to the unknown value u multiply 2 x 6
which equals 12
Answer: ![f(-735) = -\frac{2}{3}(-735) + 490 = 980](https://tex.z-dn.net/?f=f%28-735%29%20%3D%20-%5Cfrac%7B2%7D%7B3%7D%28-735%29%20%2B%20490%20%3D%20980)
Step-by-step explanation:
Subtract 490 from both sides
Then flip
multiply both sides by
to cancel out ![-\frac{2}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7D)
Thus giving you -735 as your
.
Then you plug it back into the equation to solve.
To solve both of these expressions, we want to add or subtract from left to right.
For the first one, we can rewrite it as:
8-6-9
=2-9
=-7
The second one we can rewrite as:
5-7+9+8-4
=-2+9+8-4
=7+8-4
=15-4
=11
Green beans, cheese and hamburger